2022
DOI: 10.3390/v14020354
|View full text |Cite
|
Sign up to set email alerts
|

Diphyllin Shows a Broad-Spectrum Antiviral Activity against Multiple Medically Important Enveloped RNA and DNA Viruses

Abstract: Diphyllin is a natural arylnaphtalide lignan extracted from tropical plants of particular importance in traditional Chinese medicine. This compound has been described as a potent inhibitor of vacuolar (H+)ATPases and hence of the endosomal acidification process that is required by numerous enveloped viruses to trigger their respective viral infection cascades after entering host cells by receptor-mediated endocytosis. Accordingly, we report here a revised, updated, and improved synthesis of diphyllin, and demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…For example, HSV-1 enters host cells predominantly via plasma membrane interactions and fusion at the cell surface ( White and Whittaker, 2016 ). On the other hand, the virus–cell fusion machineries of coronaviruses and flaviviruses are strictly based on receptor-mediated endocytosis, followed by lower pH-induced fusion of the viral envelope with the endosomal membrane ( Hu et al., 2017 ; Štefánik et al., 2022 ). Obviously, the perylene-based antiviral effect is independent of these differences in virus–cell entry mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…For example, HSV-1 enters host cells predominantly via plasma membrane interactions and fusion at the cell surface ( White and Whittaker, 2016 ). On the other hand, the virus–cell fusion machineries of coronaviruses and flaviviruses are strictly based on receptor-mediated endocytosis, followed by lower pH-induced fusion of the viral envelope with the endosomal membrane ( Hu et al., 2017 ; Štefánik et al., 2022 ). Obviously, the perylene-based antiviral effect is independent of these differences in virus–cell entry mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in good accordance with those of a very recent study that confirmed the anti-SARS-CoV-2 activity (IC 50 , 1.92 μM) and low cytotoxicity (IC 50 value >100 μM) in the Vero E6 host cells for 1. 8 Literature results also show that the antiviral activity of the monoglycoside of 1 against SARS-CoV-2 8 and tick-borne encephalitis virus (TBEV) 9 as well as that of the diglycoside and triglycoside of 1 against the human immunodeficiency virus 1 (HIV-1) 5 was 3.4, 6.3, 13.0, and 62.1 times lower than the antiviral activity of the free aglycone 1, respectively. Due to these results, glycosides of 1 (compounds 5−8) were not isolated from our Linum samples to test their anti-SARS-CoV-2 activity.…”
Section: Conversion Study Of Compounds and Identification By High-per...mentioning
confidence: 99%
“…They are effective in vitro antiviral agents at submicromolar concentrations against various viruses, with low toxicity in the host cells used to propagate the viruses (Supporting Table S1). Compound 1 also presents antiviral activity against Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), without expressing any toxicity against the host cells Vero and Vero E6 (both are kidney epithelial cells derived from Cercopithecus aethiops ) …”
mentioning
confidence: 99%
“…Diphyllin is an arylnaphtalide lignan extracted from plants used in the traditional Chinese medicine and exerted antiviral activity against ZIKV (Paraiba 01 strain) in Vero cells (EC 50 = 0.54 μM, CC 50 > 100 μM and SI > 185.19). When tested at concentrations between 12.5 and 25 μM, the viral surface antigen expression was eliminated in Vero cells [ 106 ].…”
Section: Nps With Potential Anti-zikv Activitymentioning
confidence: 99%